Procedural Justice and Organizational Citizenship Behaviour of Deposit Money Banks in Rivers State, Nigeria - Baridula, Vito; Mark, Dr. John (Journal of Strategic Management, 2019)
Purpose: This study investigated the relationship between procedural justice and organizational citizenship behaviour in Deposit Money Banks in Rivers State. The effects of procedural justice was tested on organizational citizenship behaviour measures such as altruism and sportsmanship. Methodology: The study adopted a cross sectional survey design and data was generated from 193 respondents from the target Deposit Money Banks in Rivers State. As a quantitative study, the primary data collection instrument for the study was the structured questionnaire. The test for the reliability for the instrument was carried out using the Cronbach alpha reliability instrument with a reliability threshold of 0.70. The Analysis comprised of the univariate (single variable assessments) bivariate (test for hypothetical relationships) while the bivariate analysis was carried out using the Spearman's rank order correlation coefficient at a 0.05 level of significance. Findings: Findings from the study revealed that workplace justice significantly impacts on the measures of OCB (altruism and sportsmanship) and also organizational culture was revealed to also significantly moderate the relationship between workplace justice and organizational citizenship behaviour in Deposit Money Banks in Rivers State. Based on the findings, it was concluded that there is significant relationship between the predictor and the measures of the criterion variables. Contribution to practice and Policy: The study recommended that OCB within an organization could be significantly increased by enhancing organizational fairness, particularly procedural justice. Bank managers should first improve the procedural justice and hence increase overall levels of perceived justice by involving employees in the procedures used in making decisions and allocating rewards